Drinking Goals and Their Association With Treatment Retention and Treatment Outcomes Among Clients in Outpatient Alcohol Treatment. (23rd February 2017) - Haug, Severin; Eggli, Peter; Schaub, Michael P.
ABSTRACT: Background : Few studies have compared characteristics of clients entering alcohol treatment who differ in their drinking goal preferences or have investigated the relevance of drinking goals as a predictor of treatment outcomes. Objectives : To investigate associations between baseline drinking goal preferences and client characteristics as well as treatment retention and outcomes among clients in outpatient alcohol treatment. Methods : Secondary data analyses on a longitudinal multicenter study investigating the effectiveness of outpatient alcohol treatment in Switzerland among 805 clients. Assessments were conducted at treatment admission, discharge, and at 6- and 12-month follow ups. At-risk drinking was assessed through the alcohol use disorders identification test. Treatment retention was defined as regular discharge with or without transition into another institution. Results : Clients aiming to abstain from drinking were more likely to be in retreatment, to be assigned to treatment by a health institution, to have no at-risk alcohol use, and to be already alcohol abstinent at the time of admission relative to clients who aimed to control their drinking. Clients without at-risk alcohol use at admission showed higher treatment retention when aiming for controlled drinking than for abstinence, while there was no difference in treatment retention among clients with at-risk use. Clients with at-risk use at admission were more likely to reach not-at-risk alcohol use status when aiming for alcohol abstinence than for controlled drinking. Conclusions : Drinking goals are associated with variables of alcohol use and treatment assignment. They have different effects on treatment retention and treatment outcomes according to alcohol use at the time of admission.